Climate policy foundations : science and economics with lessons from monetary regulation - Whitesell, William C. (Cambridge : Cambridge University Press, 2011)
This book provides a thorough grounding in the science and economics of climate policy issues and draws key lessons from the longer experiences of central banks in grappling with related challenges. Findings and controversies of climate history and the effects of human activities on climate are reviewed. The author describes similarities in risk management approaches for climate and monetary policy. Overall goals and frameworks for addressing climate change risks are assessed. Command-and-control and market-based options are compared (including performance standards, taxes and cap-and-trade). Market-based approaches sometimes require a choice between prices and quantities as policy instruments. However, the author discusses how techniques of central bank interest rate management can be adapted in a hybrid climate policy approach to achieve environmental goals while making carbon prices predictable and also ensuring well-functioning carbon markets. Key lessons are offered for improving existing and future national and international climate policy architectures.
Earth's climate history and outlook. Salient events of climate history ; Human and climate interactions ; Greenhouse gases ; Emitting economic sectors ; Forecasts of GHG emissions and global temperatures ; Potential impacts of climate change -- Climate policy choices ; Climate policy goals ; Policy mandates and market-based instruments ; The design of cap-and-trade programs ; Prices, quantities, and lessons from monetary policy ; The outlook for climate policies.
Title from publisher's bibliographic system (viewed on 24 Feb 2016).
Keywords: Environmental policy -- Economic aspects; Climatic changes -- Economic aspects; Monetary policy -- Environmental aspects